Effects of resistance training movement pattern and velocity on isometric muscular rate of force development: A systematic review with meta-analysis and meta-regression - Blazevich, A. J.; Wilson, C. J.; Alcaraz, P. E.; Rubio-Arias, J. A, (Sports Medicine, 2020)
Background: Muscular rate of force development (RFD) is positively influenced by resistance training. However, the effects of movement patterns and velocities of training exercises are unknown. Objectives: To determine the effects of velocity, the intent for fast force production, and movement pattern of training exercises on the improvement in isometric RFD from chronic resistance training. Methods: A systematic search of electronic databases was conducted to 18 September, 2018. Meta-regression and meta-analytic methods were used to compute standardized mean differences (SMD?±?95% confidence intervals) to examine effects of movement pattern similarity (between training and test exercises; specific vs. non-specific) and movement speed (fast vs. slow vs. slow with intent for fast force production) for RFD calculated within different time intervals. Results: The search yielded 1443 articles, of which 54 met the inclusion criteria (59 intervention groups). Resistance training increased RFD measured to both early (e.g., 50 ms; standardized mean difference [95% CI] 0.58 [0.40, 0.75]) and later (e.g., 200 ms; 0.39 [0.25, 0.52]) times from contraction onset, as well as maximum RFD (RFDmax; 0.35 [0.21, 0.48]). However, sufficient data for sub-analyses were only available for RFDmax. Significant increases relative to control groups were observed after training with high-speed (0.54 [0.05, 1.03]), slow-speed with intent for fast force production (0.41 [0.20, 0.63), and movement pattern-specific (0.38 [0.17, 0.59]) exercises only. No clear effect was observed for slow-speed without intent for fast force production (0.21 [0.00, 0.42], p = 0.05) or non-movement-specific (0.27 [- 0.32, 0.85], p = 0.37) exercises. Meta-regression did not reveal a significant difference between sexes (p = 0.09); however, a negative trend was found in women (- 0.57 [- 1.51, 0.37], p = 0.23), while a favorable effect was found in men (0.40 [0.22, 0.58], p < 0.001). Study duration did not statistically influence the meta-analytic results, although the greatest RFD increases tended to occur within the first weeks of the commencement of training. Conclusions: Resistance training can evoke significant increases in RFD. For maximum (peak) RFD, the use of faster movement speeds, the intention to produce rapid force irrespective of actual movement speed, and similarity between training and testing movement patterns evoke the greatest improvements. In contrast to expectation, current evidence indicates a between-sex difference in response to training; however, a lack of data in women prevents robust analysis, and this should be a target of future research. Of interest from a training program design perspective was that RFD improvements were greatest within the first weeks of training, with less ongoing improvement (or a reduction in RFD) with longer training, particularly when training velocity was slow or there was a lack of intent for fast force production.